2020
DOI: 10.33830/diseminasiabdimas.v2i1.750
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Kinerja Bisnis Melalui Strategi Pemasaran Berbasis Online Pada Ukm Produk Camilan Tradisional

Abstract: The internet is one of the technologies that is inevitable in today's digital era. One effect of the internet is also having an impact on the business world, among others, with the development of e-commerce and the decreasing number of offline retailers. therefore the use of internet / e-commerce as an alternative sale must be made by all entrepreneurs including traditional snack entrepreneurs. This research aims to be able to help SMEs to introduce products through sales through the internet and its der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Fulfilling customer satisfaction is still a significant concern in micro and medium enterprises, so marketing strategies are crucial. Previous studies revealed that internet-based marketing and global competitiveness significantly increased business capacity or MSMEs (Istiqomah, Fajaryanti, and Dewi, 2020;Nurlinda and Sinuraya, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Fulfilling customer satisfaction is still a significant concern in micro and medium enterprises, so marketing strategies are crucial. Previous studies revealed that internet-based marketing and global competitiveness significantly increased business capacity or MSMEs (Istiqomah, Fajaryanti, and Dewi, 2020;Nurlinda and Sinuraya, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Perkembangan teknologi sistem informasi e-commerce yang semakin pesat tersebut dapat dimanfaatkan oleh masyarakat dalam berbagai bidang kehidupan khususnya bagi kegiatan produktivitas BUMDES dalam memasarkan hasil produknya. Menurut (Istiqomah et al, 2020) Inovasi merupakan suatu hal yang harus dilakukan oleh perusahaan baik besar maupun kecil untuk tetap dapat bertahan untuk menghadapi perubahan dan perkembangan teknologi.…”
Section: Pendahuluanunclassified